2015
DOI: 10.1038/srep12852
|View full text |Cite
|
Sign up to set email alerts
|

Protein-Based Three-Dimensional Whispering-Gallery-Mode Micro-Lasers with Stimulus-Responsiveness

Abstract: For the first time, proteins, a promising biocompatible and functionality-designable biomacromolecule material, acted as the host material to construct three-dimensional (3D) whispering-gallery-mode (WGM) microlasers by multiphoton femtosecond laser direct writing (FsLDW). Protein/Rhodamine B (RhB) composite biopolymer was used as optical gain medium innovatively. By adopting high-viscosity aqueous protein ink and optimized scanning mode, protein-based WGM microlasers were customized with exquisite true 3D geo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 53 publications
0
21
0
1
Order By: Relevance
“…The concept of environmentally friendly optical devices 41,42 has also been demonstrated by the fabrication of a whispering-gallery-mode micro-laser 53 . Figure 6b shows the smoothness and fabrication accuracy of the disk structure that is necessary to control the gallery-mode.…”
Section: Soft Microopticsmentioning
confidence: 99%
See 2 more Smart Citations
“…The concept of environmentally friendly optical devices 41,42 has also been demonstrated by the fabrication of a whispering-gallery-mode micro-laser 53 . Figure 6b shows the smoothness and fabrication accuracy of the disk structure that is necessary to control the gallery-mode.…”
Section: Soft Microopticsmentioning
confidence: 99%
“…This micro-laser performed well in air as well as in aqueous solutions. Furthermore, Sun et al demonstrated that the device was responsive to the ionic strength of the solution, thus suggesting applications in smart microfluidic devices 53 . Cell culture, in situ guidance and capture Cell culture offers possibly the widest range of applications for proteinaceous microstructures due to the variety of cell-cell interactions and microenvironmental niches of cells.…”
Section: Soft Microopticsmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, biodegradation and biocompatibility are two of the most important factors for in-vivo biosensing [12]. In this case, a WGM microresonator made from biomaterial possessing both biodegradation and biocompatibility will be an excellent candidate for in-vivo biosensing [13]. Silk fibroin originally from Bombyx mori (i.e., silkworm), has desired properties for biosensing applications, including non-toxicity, biodegradation, biocompatibility, and high transparency in visible light band (>95 %) [14][15][16][17][18][19][20], making it a suitable material alternative for WGM resonators.…”
Section: Introductionmentioning
confidence: 99%
“…Lasers made entirely from biomaterials were also demonstrated. For example, a distributed feedback laser (DFB) was made from riboflavin doped gelatin [12] and silk [13], and whispering-gallery-mode (WGM) lasing has been achieved in water droplets [14,15] and protein microspheres [16]. …”
Section: Introductionmentioning
confidence: 99%